Вплив домiшки олова на деградацiю провiдностi в n-кремнiї при електронному опромiненнi - Kras’ko, M. M. (Publishing house "Academperiodika", 2018)
The influence of an isovalent tin impurity on the electron concentration in Cz n-Si irradiated with 1-MeV electrons has been studied both experimentally and theoretically. It is found that the Sn impurity leads to the acceleration of the conductivity degradation in electron-irradiated nSi. The effect is more pronounced in high-resistance samples, whereas the rates of electron removal from low-resistance ones are almost identical in both materials. This fact can be explained by the difference between the formation efficiency of main compensating radiation- induced defects in n-Si doped with Sn (SnV and VP complexes) and undoped n-Si (mainly, VP complexes), which depends of the concentration of phosphorus in the samples.